2021
DOI: 10.3389/fimmu.2021.652677
|View full text |Cite|
|
Sign up to set email alerts
|

The Contribution of Serum Complement Component 3 Levels to 90-Day Mortality in Living Donor Liver Transplantation

Abstract: The contributions of the complement system have been elucidated in the process of solid organ transplantation, including kidney transplantation. However, the role of complement in liver transplantation is unknown. We sought to elucidate the time-dependent changes of peritransplantational serum complement levels and the relationships with posttransplant outcomes and other immunological biomarkers. We enrolled 82 patients who underwent living-related donor liver transplantation (LDLT). Nine patients (11%) died w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Biomarkers which can predict the development of infections after LTx are of great value for the optimization of immunosuppressive therapy and prevention of infections after LTx. Complementary systems, such as measuring serum complement component 3 levels at 2 weeks after transplantation, were reported as important for predicting 90-day mortality in living donor liver transplantation [ 36 ]. Mysore has also reported that patients with the highest expression of PD-1 + Tim-3 + T cells in the memory compartment before transplantation had increased incidence of infections after liver transplantation, especially within the first 90 days [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers which can predict the development of infections after LTx are of great value for the optimization of immunosuppressive therapy and prevention of infections after LTx. Complementary systems, such as measuring serum complement component 3 levels at 2 weeks after transplantation, were reported as important for predicting 90-day mortality in living donor liver transplantation [ 36 ]. Mysore has also reported that patients with the highest expression of PD-1 + Tim-3 + T cells in the memory compartment before transplantation had increased incidence of infections after liver transplantation, especially within the first 90 days [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the increased risk of infectious complications, upregulation of inflammatory markers and downregulation of cnidarian complements in both the advancement of cirrhosis and development of CCM were associated with poor survival (21,(45)(46)(47). Similarly, NLR was considered an effector, along with SII and PLR, in this study.…”
Section: Discussionmentioning
confidence: 84%
“…Each component of the complement system activates the complement cascades through intricate interactions between various soluble products and cell surface receptors and plays a crucial role against infection (8,11). C4 has a central role in the classical pathway and has shown associations with early and late allograft function (8,12). All three activation cascades -classical, alternative, and lectin pathway-converge at the level of C3 to form C5 convertase and result in the formation of the membrane attack complex (1,10,12).…”
Section: Introductionmentioning
confidence: 99%
“…C4 has a central role in the classical pathway and has shown associations with early and late allograft function (8,12). All three activation cascades -classical, alternative, and lectin pathway-converge at the level of C3 to form C5 convertase and result in the formation of the membrane attack complex (1,10,12). Decreased levels of C3 have been reported to be associated with the occurrence of infectious complications after heart and lung transplantation (7,11,13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation